Penataan Mekanisme Seleksi Keanggotaan Komisi Pemilihan Umum (KPU) yang Independen Dan Partisipatif - aldy, Rinaldy (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
A democratic general election requires an election organizer that is independent and free from interference from any party. However, the fact that many KPU commissioners are considered not neutral and entangled in corruption cases seems to strengthen public assumptions about the low quality of KPU membership selection. This study intends to analyze the problems in the KPU membership selection mechanism, as well as to formulate the idea of ​​structuring a more independent and participatory selection mechanism in the future. In this study of normative law, a statute approach and a conceptual approach are used. The results show that the involvement of the DPR in testing candidates for KPU members is one of the gaps for the inclusion of political elements in the KPU membership selection. In the future, it is necessary to minimize the authority of the DPR in the selection mechanism. Involvement of community participation in the formation of the selection committee and the selection process is also needed to produce a higher quality selection mechanism